Hipertiroidismo e hipotiroidismo como factores de riesgo para el desarrollo de enfermedad cardiovascular en pacientes que acudieron al servicio de endocrinología del Hospital del IESS Manuel Ygnacio Monteros Valdivieso de Loja - Mogrovejo Palacios, David Ricardo (2019)
Hyperthyroidism and hypothyroidism are thyroid diseases that if they don´t receive an appropriate treatment, they can cause systemic changes, such as the cardiovascular alterations. The purpose of this study was to determine the prevalence of hyperthyroidism and hypothyroidism; establish the relationship with the parameters that condition a higher cardiovascular risk; predict the risk of cardiovascular disease and identify the cardiovascular pathologies that were diagnosed in these patients. It was a descriptive and retrospective study with quantitative approach and transversal section; it was developed with a population of 111 patients, who attended the Endocrinology service of the Manuel Ygnacio Monteros Valdivieso Hospital in the city of Loja, attended in 2015. Obtaining the following results: the female sex predominated in the population studied, the age group from 51 to 60 years prevailed in 5% of hyperthyroid patients; while patients from 61 to 70 years prevailed as hypothyroid with 21%. According to the parameters that condition a higher cardiovascular risk, overweight and obesity occurred more frequently for hyperthyroidism in 67% and hypothyroidism in 68%. Furthermore, the low cardiovascular risk in these patients prevails in 93% of the hyperthyroid population and in 75% of the hypothyroidism population. Hypertension was the most frequent cardiovascular disease diagnosed, mainly in hypothyroid patients, represented by 15%. The conclusion of this study is that if these pathologies are not properly controlled, they can lead the patient to a greater cardiovascular risk. Key words: hyperthyroidism, hypothyroidism, cardiovascular risk, body mass index, arterial hypertension.